Teachers’ occupational stress and perceived support in Finland and Estonia during the COVID-19 lockdown - Pöysä, Sanni; Jõgi, Anna-Liisa; Tammets, Kairit; Eisenschmidt, Eve; Pakarinen, Eija; Lerkkanen, Marja-Kristiina (Frontiers in Education, 2023)
This study examined teachers’ experiences of occupational stress in Finland and Estonia during the COVID-19 lockdown, and whether their stress would be related to their experiences of support from colleagues and leaders. The participants were total of 1,319 teachers that were teaching grades 1–6 in spring 2020. The data were analyzed using regression analyses with interaction terms. The results showed that the teachers in Finland and Estonia experienced stress during the lockdown, and that teachers’ stress was higher in the Finnish sample than in the Estonian sample. The findings of this study suggest that support gained from colleagues or leaders seems to be important when aiming to reduce teachers’ occupational stress in both countries.